Are aerobic fitness and repeated sprint ability linked to fatigue in professional soccer match-play? A pilot study - Carling, C.; Le Gall, F.; McCall, A.; Nedelec, M.; Dupont, G. (Journal of Athletic Enhancement, 2013)
This investigation examined the association between aerobic fitness and repeated sprint ability and match-related fatigue in 9 professional outfield soccer players. Aerobic fitness using maximal aerobic speed (MAS) was determined via a continuous progressive incremental running test conducted on a motorised treadmill. A repeated sprint ability test (6 successive 6 s sprints separated by 20 s passive recovery) was performed on a non-motorised treadmill to determine mean and best sprint times and a percentage decrement score (%PD). A total of 114 observations of physical performance derived using computerised time motion analyses were collected from 33 matches. Correlations between fitness test and match-play measures were examined for 1) accumulated fatigue: percentage difference between halves for total distance covered per minute, distance run at high-intensities (HIR, actions for 1s duration, >19.1 km/h) per minute, mean recovery time between high-intensity runs, and percentage difference between the distance covered in HIR in the first 5- and 15-minute periods versus the final 5- and 15-minute periods respectively in normal time; and for 2) transient fatigue: percentage difference between the distance covered in HIR in a peak 5-minute period and the subsequent 5-minute period and for the latter compared to the mean for all other 5-minute periods. No significant relationships were observed between MAS and fatigue scores (magnitude of associations: trivial to large). For mean and best sprint times and %PD, the only reported significant correlation (r=0.77, magnitude of association: very large, p<0.05) was between %PD and the % difference across halves for mean recovery time between high-intensity runs (magnitude of other associations: small to large). Criterion measures from tests of aerobic fitness and repeated sprint ability might not accurately depict a player`s capacity to resist fatigue during professional soccer competition.